Mediating Fruitful Encounters With Truth, Transcendence, and Difference by Teaching Critical Thinking - Manning, Patrick R. (2018)
Cultivating a disposition of critical thinking among students and faculty can provide a means of addressing troubling cultural trends like breakdowns in public discourse, academic siloing, and disengagement from religion. This article expands the concept of critical thinking by engaging the work of John Henry Newman and Bernard Lonergan. The latter part of the article narrates how one university has integrated Lonergan's "generalized empirical method" into the curriculum and faculty development with promising outcomes for collaboration across disciplines, faculty spirituality, and facilitating difficult conversations on campus.